The Philippine Universal Health Care Law: A Differing View - Gene Alzona Nisperos; Eric David Bicaldo Ornos (Social Medicine Publication Group, 2022)
The World Health Organization espouses Universal Health Care (UHC) as a means to address health inequity and allow the poorest sections of the population to access health care. In the Philippines, government efforts to implement this have evolved over the last ten years, resulting in the passage of the Universal Health Care Act in 2019. The law relies heavily on health financing as the central driver of the healthcare system reforms. This article describes and analyzes key actors on the implementation of the UHC Act, particularly the insurance program it is anchored on, the agency that will be primarily tasked to implement it, and the overarching principle behind the law. These are burdened with problems and may be anathema to the outcomes sought. Rather than a health financing-based direction in health development, a rights-based approach is posited to be a better framework and roadmap to achieve health for all.